P16.05 CHARACTERISING REGIONAL HETEROGENEITY OF GLIOBLASTOMA USING MULTIMODAL IMAGING: REGIONS OF AGGRESSIVE GROWTH - Boonzaier, N.R. (Oxford University Press, 2014)
BACKGROUND: Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumour. Understanding intra-tumour heterogeneity associated with GBM, which is considered a primary contributing factor to treatment failure, involves the analysis of tumour tissue obtained using biopsy samples. Due to the risks involved in performing multiple biopsies on patients, non-invasive methods are needed for tumour analysis. This study aimed to identify imaging signatures of aggressive tumour belonging to different regions of high-grade gliomas using multimodal imaging methods, including diffusion-weighted imaging and MR spectroscopy. METHODS: 32 Patients (mean age 57.2, range 28-75 years) with confirmed GBM were imaged at 3T on a Siemens Trio. Maps of apparent diffusion coefficient (ADC) were coregistered to T2-weighted images. Regions of interest (ROIs) were selected per tumour: FLAIR enhancement with T1-weighted post-contrast enhancement (CE); and FLAIR enhancement without CE (FLAIR). Within these sub-regions, an ADC cut-off value was developed using MATLAB. Metabolic maps of choline/N-acetylaspartate (Cho/tNAA) ratios belonging to these ADC ROIs were calculated using LCModel to determine whether they demonstrated metabolic features of aggression as described in the literature, where a higher ratio value indicates more aggressive tumour. Metabolic ratios from CE and FLAIR were compared to each other and to ratios of ROIs above the ADC threshold within tumour (high ADC) and contralateral normal appearing white matter (NAWM). RESULTS: Metabolic results were obtained for CE in 11/32 patients, and for FLAIR in 29/32 patients. When comparing Cho/tNAA ratio mean values of CE and FLAIR to NAWM (0.26 ± 0.09), both low ADC tumour regions demonstrated ratio means that were significantly higher than those of NAWM (0.60 ± 0.21, p < 0.001; 0.45 ± 0.22; p < 0.001 for CE and FLAIR, respectively). ROIs of high ADC had a mean ratio value (0.39 ± 0.16) that was significantly lower than that of CE (p < 0.01). CONCLUSION: Findings suggest that regional heterogeneity of GBM can be detected and possibly characterised using advanced imaging. Low ADC ROIs within CE regions appear to have metabolic profiles representing aggressive tumour. Combining imaging modalities could potentially help differentiate regions that will respond/fail to respond to treatment.